2014
DOI: 10.1002/2013jc009528
|View full text |Cite
|
Sign up to set email alerts
|

Cyclogeostrophic balance in the Mozambique Channel

Abstract: Three methods are proposed for the inclusion of inertia when deriving currents from sea surface height (SSH)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 28 publications
0
64
0
Order By: Relevance
“…For anticyclonic features with large g 0 leading to large u g , the sum under the square root sign can become negative as r gets close to zero. This effect was noted in Penven et al [2014], who showed that for large g 0 , the gradient wind equation has no solution for small radii. The fact that the solution only exists within a limited range should be taken into consideration when calculations are completed.…”
Section: Idealized Casementioning
confidence: 86%
“…For anticyclonic features with large g 0 leading to large u g , the sum under the square root sign can become negative as r gets close to zero. This effect was noted in Penven et al [2014], who showed that for large g 0 , the gradient wind equation has no solution for small radii. The fact that the solution only exists within a limited range should be taken into consideration when calculations are completed.…”
Section: Idealized Casementioning
confidence: 86%
“…This latter force needs to be taken into account, otherwise, the velocity is underestimated for anticyclones and overestimated for cyclones [Elliott and Sanford, 1986;Penven et al, 2014]. The cyclostrophic velocities v c can be retrieved by solving the quadratic equation expressing the gradient wind balance in a cylindrical coordinate system: To infer cyclostrophic velocities, (1) the eddy center position and (2) absolute geostrophic velocities have to be determined.…”
Section: Appendix A: Solving the Gradient Wind Balance With Glidersmentioning
confidence: 99%
“…Momentum equations can be then easily solved, giving rise to the gradient wind solution (e.g., Holton, 1992). This provides a first correction to the geostrophic velocities derived from altimetry, which can be up to 50 % of the geostrophic velocity in intense vortices (Penven et al, 2014). This correction, which depends on the curvature of the streamlines, can be implemented using the iterative method proposed by Endlich (1961) and Arnason et al (1962):…”
Section: Currents From Sea Surface Heightmentioning
confidence: 99%
“…The iterations stop once the velocity increment falls below a threshold or it starts to increase (Penven et al, 2014).…”
Section: Currents From Sea Surface Heightmentioning
confidence: 99%